CLOCK DRAWING TEST – KOGNITIV FUNKCIYALARDÍŃ ZAQÍMLANÍWÍNÍŃ GILTI SÍPATÍNDA - Turdımuratova, A.B. (SCIENCE and SOCIETY, 2025)
The article analyzes the potential applications of the projective technique known as the Clock Drawing Test (CDT) within both clinical and educational psychology. The CDT is identified as an effective tool for evaluating cognitive and emotional aspects of personality by analyzing a clock drawing that reflects a specific time. The method is widely employed for the early detection of cognitive impairments, as well as for assessing spatial-temporal perception, attention, memory, motor coordination, and executive functioning. Common errors made during the task are highlighted as key indicators of cognitive dysfunction. The article provides an overview of interpretive strategies, including qualitative, quantitative, and mixed-method approaches. In educational settings, the test is adapted to evaluate children’s abilities to orient themselves in time and space. The findings emphasize the high diagnostic value of the CDT and its effectiveness as a universal neuropsychological screening instrument.
Keywords: clock Drawing Test (CDT); cognitive disorders; spatial perception; neuropsychology; early diagnosis; dementia; child psychodiagnostics; executive functions; attention and memory; error analysis